2021
DOI: 10.1530/joe-21-0171
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid maturation of mitochondrial respiratory capacity in skeletal muscle before birth

Abstract: In adults, glucocorticoids act to match the supply and demand for energy during physiological challenges, partly through actions on tissue mitochondrial oxidative phosphorylation (OXPHOS) capacity. However, little is known about the role of the natural prepartum rise in fetal glucocorticoid concentrations in preparing tissues for the increased postnatal energy demands. This study examined the effect of manipulating cortisol concentrations in fetal sheep during late gestation on mitochondrial OXPHOS capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Neither CS activity nor mitochondrial OXPHOS capacity normalised to CS activity were affected by cortisol infusion in the fetuses, regardless of the specific substrate or muscle, consistent with previous measurements of CS activity per mg BF protein in cortisol-infused fetal sheep. 22 However, by adulthood, PCM-supported respiration was 60-70% higher than control values in the ST of animals that received cortisol as fetuses. Fetal exposure to higher than normal levels of cortisol in late gestation can, therefore, have longer term effects on mitochondrial substrate metabolism and may enhance the capacity of adult sheep to use fatty acids for OXPHOS in selective muscles.…”
Section: Discussionmentioning
confidence: 93%
“…Neither CS activity nor mitochondrial OXPHOS capacity normalised to CS activity were affected by cortisol infusion in the fetuses, regardless of the specific substrate or muscle, consistent with previous measurements of CS activity per mg BF protein in cortisol-infused fetal sheep. 22 However, by adulthood, PCM-supported respiration was 60-70% higher than control values in the ST of animals that received cortisol as fetuses. Fetal exposure to higher than normal levels of cortisol in late gestation can, therefore, have longer term effects on mitochondrial substrate metabolism and may enhance the capacity of adult sheep to use fatty acids for OXPHOS in selective muscles.…”
Section: Discussionmentioning
confidence: 93%
“…The administration of potent synthetic glucocorticoids during rodent pregnancy has also been shown to increase the mitochondrial content in the fetal lung [ 26 ] and kidney [ 27 ], and alter the abundance of mitochondrial proteins in fetal tissues near term, such as the brain [ 28 ], kidney [ 27 ] and heart [ 29 ]. Recent studies have also shown that variations in the endogenous cortisol concentration affect CS activity in ovine fetal skeletal muscle [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult mitochondria are dynamic organelles that respond to changes in energy demands by biogenesis and alterations in the electron transfer system (ETS) complexes and other proteins regulating ATP synthesis, including those supporting oxidation of specific substrates [ 98 ]. Glucocorticoids are known to influence many of these regulatory processes in adult tissues and recent studies have shown that they also have an important role in the normal prepartum maturation of mitochondrial OXPHOS capacity in cardiac and skeletal muscle [ 74 , 99 , 100 , 101 , 102 ].…”
Section: Effects Of Glucocorticoids On Feto-placental Metabolismmentioning
confidence: 99%
“…Maternal dexamethasone administration to pregnant ewes near term also increases the abundance of mitochondrial ETS and uncoupling proteins in perirenal adipose tissue of their fetuses in line with the need for non-shivering thermogenesis at birth [ 56 , 73 ]. Similarly, direct cortisol infusion into fetal sheep in late gestation increases mitochondrial content and respiratory capacity of skeletal muscle in a manner that depends on the specific oxidative substrate and muscle studied [ 74 ]. Furthermore, raising fetal corticosterone indirectly in fetal rats in late gestation by ligating the uterine artery also increases expression of several ETS complexes in a range of fetal tissues two days later [ 104 , 105 ].…”
Section: Effects Of Glucocorticoids On Feto-placental Metabolismmentioning
confidence: 99%
See 1 more Smart Citation